Pengaruh Edukasi tentang Perencanaan Kehamilan dan Kesehatan Reproduksi terhadap Pengetahuan Pasangan Usia Subur - Afiyah Karim; Fidyawati Hiola; Yuliandary Yunus; Fatmah Zakaria (STIKes Hamzar, 2026)
The high number of maternal deaths in Indonesia demonstrates the importance of health promotion efforts, particularly regarding pregnancy planning and reproductive health. This study aimed to determine the effect of pregnancy planning and reproductive health education on the knowledge of fertile couples in the Dungingi Community Health Center (Puskesmas). The study employed a single-group pre-experimental design with a pretest and posttest, involving 30 fertile couples selected using a simple random sampling method. The instruments used in this study were a questionnaire and educational media in the form of a booklet. Data were analyzed using univariate and bivariate methods using the Wilcoxon test. The results showed that before the education, respondents' knowledge was categorized as poor (16.7%), sufficient (73.3%), and good (10%). After the education, the sufficient category decreased to 53.3%, the good category increased to 46.7%, and the poor category decreased to 0%. The average knowledge score also increased from 13.10 (SD=1.72) in the pretest to 15.30 (SD=1.44) in the posttest. The Wilcoxon test showed a p-value of 0.000, indicating a significant effect of education in improving the knowledge of fertile couples. The conclusion of this study is that education about pregnancy planning and reproductive health is effective in improving the knowledge of fertile couples. This intervention should be implemented routinely, especially for young people and those with secondary education, using easy-to-understand media such as booklets. It is recommended for health workers to expand similar educational programs in primary care facilities to support healthy pregnancy preparedness and reduce the risk of unsafe pregnancies.